L'hospitalité des humains envers les jnûn - Araceli González Vázquez (Revue d'ethnoécologie)
Hospitality, in particular its normative character, is one of the classical themes of social anthropology, often dealt with in relation to Mediterranean societies. Despite a renewed interest for the theme of hospitality in social anthropology, both the imaginary and the practice of interspecific hospitality remain little explored, notably what they tell us, for example, on the conceptions of otherness, humanity and animality, on local ontologies, on ethical reasoning, on the ritual activity of women and men, and on the relations between living beings, particularly on the relationship between human beings and non-human beings. Our article is part of this line of reflection on the Other, and is especially interested in exploring the stakes of interspecific hospitality in Northern Morocco.